Spiral antenna with reconfigurable HIS using liquid crystals for monopulse radar application - Mohamad, Sarah Yasmin; Cahill, Robert (Institute of Electrical and Electronics Engineers Inc., 2017)
In this paper, the design of an electronically reconfigurable ground plane composed of a high impedance surface (HIS) based on liquid crystals is presented and used as a backing structure for a two-arm Archimedean spiral antenna. The structure is used to provide electronic switching of two different shaped radiation patterns for monopulse radar application; 1) sum-pattern (Σ-pattern), and 2) difference pattern (Δ-pattern). The antenna arrangement is shown to exhibit either the Σ- or the Δ-beam by changing the permittivity (and hence reflection phase) of the HIS reflector when a bias voltage is applied between the periodic array and ground plane. The HIS is demonstrated to resonate at 6 GHz, and numerical results are employed to investigate the performance of the HIS-backed spiral arrangement, i.e. radiation pattern, impedance match, realized gain (Σ-pattern), and null depth (Δ-pattern).